Effect of mechanical recycling on the properties of a composite material based on polyvinyl chloride loaded with olive husk flour - KLAAI, Lisa (Biopolymer Applications Journal, 2023)
In this article, we try to contribute to the development of methods and strategies necessary to transform olive husk (OH) from waste for disposal into valuable raw materials as bio-filler for the PVC, for providing a composite with very high physical-mechanical and thermal characteristics interesting.Several formulations of composite materials based on PVC (as a matrix), olive husk (as filler) and a PVC-g-MA coupling agent, have been the subject of study experiments to assess the structural-mechanical and thermal properties. Investigate the combined effect of olive husk flour, PVC-g-MA and recycling on composite properties. The results showed that the mechanical properties of the composites increase with the number of extrusion cycles, the tensile strength and the Young's modulus in the studied formulations increased considerably. On the other hand, the infrared spectra show no significant change after four extrusion cycles. It is also important to take into account the evolution of the thermal properties of the composites after the transformation cycles. We noticed that the addition of olive husk flour causes a slight decrease in the temperature of onset of degradation.